1438. Uptake of 13-Valent Pneumococcal Conjugate Vaccine in High-Risk Adults Aged 19–64 Years: A Kaplan–Meier Approach. (26th November 2018) - Vietri, Jeffrey; Emir, Birol; Harnett, James; Chilson, Erica
Abstract: Background: Coverage estimates for pneumococcal vaccination in the United States come from the National Health Interview Survey (NHIS) and do not differentiate between 13-valent conjugated vaccine (PCV13) and 23-valent polysaccharide vaccine (PPSV23). This study was conducted to assess coverage of PCV13 among adults aged 19–64 years targeted by the high-risk recommendation issued by the Advisory Committee on Immunization Practices (ACIP) in 2012. Methods: Uptake was evaluated from October 2012 through October 2016 in two statistically de-identified databases: Optum's Clinformatics™ Data Mart (CDM), consisting of administrative health claims, and the Optum-Humedica Electronic Health Record (EHR) dataset, which includes EHR data from providers, primarily integrated delivery networks in the United Statess to cover the continuum of care. Eligibility for the recommendation was determined between October 2011 and October 2016 and served as the index event. Post-index PCV13 uptake was evaluated using prescription and administration codes. Patients with PCV13 prior to the recommendation were excluded to minimize misclassification of PCV13 status. Uptake was calculated using a Kaplan–Meier estimator, with separate estimates for the period before and after the 2014 ACIP age-based recommendation for all adults aged ≥65 years. Results: Uptake of PCV13 was lower among 223, 888 patients in the CDM vs. 571, 993 patients in the EHR dataset, with < 15% of recommended high-risk patients receiving PCV13 in the 4 years following publication of the recommendation. Vaccination among 19- to 64–year-old high-risk patients accelerated after the October 2014 publication of the recommendation for all adults aged ≥65 years. This was consistent in both CDM and EHR databases (Table 1). Conclusion: Uptake of PCV13 among high-risk adults aged 19–64 years in the US has been very low. Some of the PCV13 vaccination among high-risk patients may have been driven by spillover from the subsequent age-based recommendation for adults aged ≥65 years. Disclosures: All authors : Employee and Shareholder, Salary.